Recent Progress in Nanomedicine for Melanoma Theranostics With Emphasis on Combination Therapy - Guan, Mengqi; Zhu, Shoujun; Li, Shanshan (Frontiers in Bioengineering and Biotechnology, 2021)
Melanoma is a very aggressive type of skin cancer with increasing incidence worldwide and high mortality rates. However, there is still a lack of efficient and resolutive treatment strategies, particularly in clinical settings. Currently, nanomedicine, an emerging area in the medical field, is being widely investigated in small animal models to afford melanoma theranostics. However, several problems, such as tumor heterogeneity and drug resistance treatment with a single therapy, remain unresolved. Available reviews have primarily focused on monotherapy for melanoma with nanomedicine. In this review article, we summarize the recent progress in the application of nanomedicine for melanoma treatment, with particular attention to combination therapy based on nanomedicine to achieve optimized therapeutic output for melanoma treatment. In addition, we also highlight the fluorescence-guided strategies for intraoperative melanoma detection, especially in the near-infrared imaging window with greatly improved imaging contrast and penetration depth.